A review of silicon carbide MOSFETs in electrified vehicles: Application, challenges, and future development - Bufan Shi; Anna Isabel Ramones; Yingxu Liu; Haoran Wang; Yu Li; Stefan Pischinger; Jakob Andert (IET Power Electronics, 2023)
Abstract Compared with silicon‐based Insulated Gate Bipolar Transistors (IGBTs), silicon carbide (SiC) Metal‐Oxide‐Semiconductor Field‐Effect Transistors (MOSFETs) are characterized by higher operating temperatures, switching speeds and switching frequencies, and are considered the next evolutionary step for future electric drives. The application of SiC MOSFETs in the field of electrified vehicles has brought many benefits, such as higher efficiency, higher power density, and simplified cooling system, and can be seen as an enabler for high‐power fast battery charging. This article reviews the benefits of SiC MOSFETs in different electrified vehicle (EV) application scenarios, including traction inverters, on‐board converters, and off‐board charging applications. However, replacing Si‐IGBTs with SiC MOSFETs introduces several new technical challenges, such as stronger electromagnetic interference (EMI), reliability issues, potential electric machine insulation failure due to high transient voltages, and cooling difficulties. Compared to mature silicon‐based semiconductor technologies, these challenges have so far hindered the widespread adoption of SiC MOSFETs in automotive applications. To fully exploit the advantages of SiC MOSFETs in automotive applications and enhance their reliability, this paper explores future technology developments in SiC MOSFET module packaging and driver design, as well as novel electric machine drive strategies with higher switching frequencies, and optimized high‐frequency machine design.